Pengaruh Struktur Kepemilikan, Kinerja Keuangan, Dan Ukuran Perusahaan Terhadap Indikasi Kesulitan Keuangan: Studi Empiris Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016-2019 - Andani, Tiara Ayu; Puspitasari, Elen (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
This reserach aims to determine what can affect financial distress in mining companies and to examine and analyze the impact of the independent variable on the dependent variable. The independent variables used in this research are ownership structure, financial performance and firm size. This research is processed using secondary data types. Tests in this research used descriptive statistics and multiple linear regression analysis to analyze the data. By using the sampling method with purposive sampling technique, 160 data were obtained where this research was processed using the SPSS version 25 program, and the population studied included mining companies listed on the IDX during the 2016-2019 period. This reserach shows that: Institutional Ownership, Liquidity, Leverage, Profitability shows a significant impact on Financial Distress. It is inversely proportional to Managerial Ownership and Company Size which indicate does not have effect on Financial Distress